Coloured Petri nets for abstract test generation in software engineering. (20th December 2022) - Sobrinho, Álvaro; Almeida, Ially; da Silva, Leandro Dias; Chaves e Silva, Lenardo; Araújo, Adriano; Costa, Tássio Fernandes; Perkusich, Angelo
Summary: Model‐based testing (MBT) relies on models of the system's behaviour to generate abstract tests. Testers can reuse formal models using MBT to increase confidence in critical systems (e.g., medical and avionic systems). In this article, we investigate the current abstract test generation approaches for CPN to provide insights for testers who need to select a suitable one when applying the MBT using CPN. We conduct a systematic literature review to investigate the existing abstract test generation approaches designed for CPN. Subsequently, focusing on specific implementations and advantages/disadvantages, we experiment with formal models of medical systems during our empirical analysis to improve the discussion on existing abstract test generation approaches for CPN. Our study shows that CPN provides reliable tests quickly, depending on the abstract test generation approach applied. Abstract : A systematic literature review and an experiment with formal models of medical systems guided a comprehensive discussion on the abstract test generation from Coloured Petri Nets (CPN) models. The analyses show that CPN provides reliable tests quickly, depending on the abstract test generation approach applied.